Bipredictive configural frequency analysis of small sample MANOVA designs - Müller, Matthias J.; Stemmler, Mark (Psychologische Beiträge, 2000)
Suggests and demonstrates an exact version of bipredictive Configural Frequency Analysis (CFA) for use in multivariate analysis of variance (MANOVA) designs with small samples. In 2 dimensional contingency tables bipredictive CFA is based on Kimball's (1954) chi-square decomposition. The sample used was from a study of acoustic vigilance experiment on 24 Ss in Germany (H. F. L. Meyer-Bahlburg, 1970). The authors emphasize that the application of Kimball's asymptotic chi-square decomposition is more applicable to larger samples.